2009
DOI: 10.1002/cmdc.200800251
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Analysis of the Peptide Deformylase Inhibitor 5‐Bromo‐1H‐indole‐3‐acetohydroxamic Acid

Abstract: The lead compound 5-bromoindolyl-3-acetohydroxamic acid (10) was recently identified as a potent inhibitor of bacterial peptide deformylases (PDFs). The synthesis and associated activities of new variants were investigated at position 5 to optimize the fit at the S1' subsite and at position 1 to improve both potency and antibacterial activity. A morphomimetic series, termed "reverse-indole" was synthesized. The indole derivatives remain selective in vitro inhibitors of PDF2 over PDF1. Bromide is the best group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
(45 reference statements)
1
24
1
Order By: Relevance
“…The NMR spectra of the products 3aa, [8] 3ba, [8] 3ca, [9] 3da, [10] 3fa, [11] 3ha, [12] 3ja [11] and 3ka [13] are in accordance with those in the literature. concentration were screened, and it was found that only a 1.2:1.0 ratio of indole/benzyl bromide was required for an efficient conversion, thereby preventing the use of a large excess of reagents without any concentration influence.…”
Section: Resultssupporting
confidence: 85%
“…The NMR spectra of the products 3aa, [8] 3ba, [8] 3ca, [9] 3da, [10] 3fa, [11] 3ha, [12] 3ja [11] and 3ka [13] are in accordance with those in the literature. concentration were screened, and it was found that only a 1.2:1.0 ratio of indole/benzyl bromide was required for an efficient conversion, thereby preventing the use of a large excess of reagents without any concentration influence.…”
Section: Resultssupporting
confidence: 85%
“…Actinonin was used as reference molecule to characterize the antibacterial activities of the newly produced PDF-Is for which an in vitro activity has been previously reported [19]. In Table 1 were presented the results obtained on isogenic strains in the absence or in the presence of various sub-inhibitory concentrations of the cyclic peptide antibiotic polymyxin B (Pol B) or its derivative the polymyxin nonapeptide (PMBN) known to increase membrane permeability [25], [26].…”
Section: Resultsmentioning
confidence: 99%
“…Most of them such as actinonin, the main characterized inhibitor, are pseudopeptidic molecule [17]. Recently we described a new series of heterocyclic compounds, with an indol scaffold, that inhibit efficiently bacterial PDF in the nM range [18], [19]. Two main mechanisms mediating resistance to peptide deformylase inhibitors in bacteria have been previously described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedure for Vilsmeier-Haack reaction followed by LiAlH 4 reduction was adapted from Petit et al 16 In a flame-dried flask under nitrogen, POCl 3 (0.42 mL, 4.6 mmol) was added at 0 °C to 4-methyl-1 H -indole (0.5 g, 3.8 mmol) in DMF (7.6 mL). The reaction was stirred at room temperature overnight.…”
Section: Methodsmentioning
confidence: 99%